Context, governance, associational trust and HRM: diversity and commonalities. Issue 17 (4th October 2021) - Goergen, Marc; Chahine, Salim; Brewster, Chris; Wood, Geoffrey
Abstract: This study explores how HRM and trust are inter-related, and what this means for how we understand HRM under different varieties of capitalism. We explore the direct impact of different indicators of societal trust on intra-organisational HRM practice, using large-scale internationally comparative survey evidence. We find that countries with high levels of associational trust, such as the Nordic social democracies, are generally associated with better communication and co-determination over the setting of the employment contract. The converse was true for countries with lower levels of associational trust, such as the liberal market economies. We failed to encounter any significant effects of multi-nationality or country of origin in the case of MNCs; they did not differ significantly from their domestic peers when it came to the relationship between country of domicile levels of associational trust and HRM practice. We draw out the implications for theory and practice.